2012
DOI: 10.1142/s0217732312502276
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Thermodynamics and Modified Gup Consistent With Doubly Special Relativity

Abstract: We study the black hole thermodynamics and obtain the correction terms for temperature, entropy, and heat capacity of the Schwarzschild black hole, resulting from the commutation relations in the framework of Modified Generalized Uncertainty Principle suggested by Doubly Special Relativity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Recently it has been revealed, in the context of doubly special relativity (DSR), that a test particles' momentum cannot be arbitrarily imprecise and therefore there is an upper bound for momentum fluctuations. Based on DSR, a new form of GUP was proposed 24,30,72 […”
Section: Massless Dirac Equation Under the Gupmentioning
confidence: 99%
“…Recently it has been revealed, in the context of doubly special relativity (DSR), that a test particles' momentum cannot be arbitrarily imprecise and therefore there is an upper bound for momentum fluctuations. Based on DSR, a new form of GUP was proposed 24,30,72 […”
Section: Massless Dirac Equation Under the Gupmentioning
confidence: 99%
“…Such a difference reflects the essential improvements in constructing the linear GUP approach [20,21]. Furthermore, correction terms for temperature, entropy, and heat capacity of Schwarzschild black hole are obtained from the commutation relations in the framework of modified uncertainty principle suggested by DSR [47]. The authors utilized quadratic GUP [15,16] and GUP-DSR [48] approaches.…”
Section: Jcap07(2013)040mentioning
confidence: 99%
“…Based on the GUP, it was found that there is no existence of black holes at LHC in [22]. The black hole thermodynamics was discussed in [23][24][25][26], respectively. The relation between the area and entropy and the corrected Hawking temperatures were gotten.…”
Section: Introductionmentioning
confidence: 99%